Enhanching Students’ Mathematical Critical Thinking Skills through Google Sites-Assisted Problem Based Learning on Junior High School - Dewi, Mera Komala; Hendriana, Heris; Supriatna, Tatang; Yuliani, Anik ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2025)
The prevalence of students experiencing difficulties in applying mathematics in their daily lives can be attributed to the predominant approach of learning mathematics as a means of applying concepts, rather than as a foundation for learning. This research aims to improve students' mathematical critical thinking skills whose learning is based on Problem-Based Learning assisted by Google Sites. This research used a quasi-experimental research method with a quantitative approach which was carried out at SMPN 2 Cilaku Cianjur with a sample of 30 students in the experimental class and 31 students in the control class on Statistics material. The testing requirements for data analysis used consist of a normality test using Kolmogorov-Smirnov assisted by SPSS software. In this research, it was found that the average score of students in the experimental and control classes was 73.76 and 64.72 on the test before learning was carried out. Then 77.87 and 68.69 on the test after learning. So the average value of N-Gain in the experimental and control classes is 0.20 and 0.10. So, inferential statistical testing shows that the improvement that occurs in students' mathematical learning in the process of critical thinking skills with the Problem-Based Learning learning model assisted by Google Sites is very optimal when compared with conventional learning. Thus, for further research, it is hoped that an analysis of the Problem-Based Learning model can be carried out in comparison with other learning models to see whether some differences and interactions occur using the Analysis of Variance test.